The Ethical Standard and Work Values of Senior High School Teachers in Libertad National High School, Surallah, South Cotabato - Obando, Jhera May F. (International Journal of Research in Interdisciplinary Studies, 2025)
This paper presents a study on the ethical standard and work values of senior high school teachers in Libertad National High School, Surallah, South Cotabato.